Temperature-Dependent Mechanical Properties of CoCrFeNi Medium-Entropy Alloy Produced by Laser-Directed Energy Deposition - Margarita Klimova; Igor Krasanov; Ilya Astakhov; Ekaterina Kovalenko; Elizaveta Kochura; Anastasia Semenyuk; Sergey Zherebtsov; Olga Klimova-Korsmik; Nikita Stepanov (Metals)
The temperature dependence of the mechanical properties of the CoCrFeNi medium-entropy alloy (MEA) manufactured by laser-directed energy deposition (L-DED) and additionally annealed at 1200 °C for 24 h was studied. The microstructure of the as-deposited alloy was represented by a single-phase face-centered cubic structure with coarse columnar grains and a high density of dislocation. Annealing resulted in the development of recrystallization and a reduction in dislocation density. The CoCrFeNi alloy produced by L-DED demonstrated mechanical properties comparable with those of the fine-grained equiatomic CoCrFeMnNi alloy, produced by casting followed by thermomechanical processing. Namely, as-deposited CoCrFeNi had a yield strength (YS) and ultimate tensile strength (UTS) of YS = 370 MPa and UTS = 610 MPa at room temperature, and YS = 565 MPa and UTS = 965 MPa at cryogenic temperature, along with a ductility of ~60%. Annealing resulted in a decrease in strength to YS = 180/350 MPa at 293/77 K. A quantitative analysis of various strengthening mechanisms showed that some strength increment of the as-deposited alloy was ensured by the high dislocation density formed during L-DED.